PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW IV UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS X IPA.4 SMA NEGERI 9 PEKANBARU: Application of Cooperative Learning Model of Jigsaw IV Type to Improve PKN Learning Outcomes of Class X IPA.4 Students of SMA Negeri 9 Pekanbaru - suhada hamsi (Perspektif Pendidikan dan Keguruan, 2019)
This study aims to determine the application of the Jigsaw IV learning model can improve PKn learning outcomes of students of class X IPA.4 Pekanbaru 9 High School. As the subjects in this study were class X IPA.4 Pekanbaru 9 High School 2017/2018 Academic Year which amounted to 38 students. The measured variable is the Jigsaw IV learning model can improve PKn learning outcomes, student learning outcomes obtained through observation sheets of teacher activity, observation of student activities and student learning outcomes. Based on the results of research that has been done, it was found an increase in PKn learning outcomes of students from the learning outcomes obtained by students, using the application of the Jigsaw IV learning model can improve PKn learning outcomes, which carried out 2 cycles, in the first cycle in the application of Students' Jigsaw IV learning model the target is 29 students or 76%, while in cycle 2 there is an increase of 32 students or 84% stated to meet the KKM standard, only 16% are declared incomplete or as many as 6 people. The application of IV jigsaw learning model can improve student learning outcomes.Keywords: Learning Model, Cooperative, Jigsaw IV Type, and Learning Outcomes.